Investigation of Tinnitus Patients in Italy: Clinical and Audiological Characteristics. (1st June 2010) - Martines, Francesco; Bentivegna, Daniela; Di Piazza, Fabiola; Martines, Enrico; Sciacca, Vincenzo; Martinciglio, Gioacchino
Abstract : Objective . 312 tinnitus sufferers were studied in order to analyze: the clinical characteristics of tinnitus; the presence of tinnitus-age correlation and tinnitus-hearing loss correlation; the impact of tinnitus on subjects' life and where possible the etiological/predisposing factors of tinnitus. Results . There is a slight predominance of males. The highest percentage of tinnitus results in the decades 61–70. Of the tinnitus sufferers, 197 (63.14%) have a hearing deficit (light hearing loss in 37.18% of cases). The hearing impairment results of sensorineural type in 74.62% and limited to the high frequencies in 58.50%. The tinnitus is referred as unilateral in 59.93%, a pure tone in 66.99% and 10 dB above the hearing threshold in 37.7%. It is limited to high frequencies in 72.10% of the patients with sensorineural hearing loss (SNHL) while the 88.37% of the patients with high-frequency SNHL have a high-pitched tinnitus (χ 2 = 66.26; P < .005 ). Conclusion . Hearing status and age represent the principal tinnitus related factors; there is a statistically significant association between high-pitched tinnitus and high-frequency SNHL. There is no significant correlation between tinnitus severity and tinnitus loudness confirming the possibility that neural connection involved in evoking tinnitus-related negative reactions are governed by conditioned reflexes.